Bottlenecks in bog pine multiplication by somatic embryogenesis and their visualization with the environmental scanning electron microscope - Vlašínová, Helena; Neděla, Vilem; Đorđević, Biljana; Havel, Ladislav (Protoplasma, 2017)
Somatic embryogenesis (SE) is an important biotechnological technique used for the propagation of many pine species in vitro. However, in bog pine, one of the most endangered tree species in the Czech Republic, limitations were observed, which negatively influenced the development and further germination of somatic embryos. Although initiation frequency was very low-0.95 %, all obtained cell lines were subjected to maturation. The best responding cell line (BC1) was used and subjected to six different variants of the maturation media. The media on which the highest number of early-precotyledonary/cotyledonary somatic embryos was formed was supplemented with 121 μM abscisic acid (ABA) and with 6 % maltose. In the end of maturation experiments, different abnormalities in formation of somatic embryos were observed. For visualization and identification of abnormalities in meristem development during proliferation and maturation processes, the environmental scanning electron microscope was used. In comparison to the classical light microscope, the non-commercial environmental scanning electron microscope AQUASEM II has been found as a very useful tool for the quick recognition of apical meristem disruption and abnormal development. To our knowledge, this is the first report discussing somatic embryogenesis in bog pine. Based on this observation, the cultivation procedure could be enhanced and the method for SE of bog pine optimized.
Keywords: Wetlands; semena rostlinná; Environmental scanning electron microscope; Microscopy, Electron, Scanning; mokřady; somatická embryogeneze rostlin; Abnormalities; Somatic embryogenesis; Seeds; borovice; klíčení; Plant Somatic Embryogenesis Techniques; Pinus uncinata subsp. uliginosa; Germination; Pinus; mikroskopie elektronová rastrovací